Survey of Ochratoxin A in South African Wines - Stander, M.A.; Steyn, P.S. (South African Journal of Enology and Viticulture, 2017)
The mycotoxin, ochratoxin A (OTA), an important nephrotoxin, teratogen and carcinogen, is mainly produced as a secondary metabolite of Aspergillus and Penicillium species. The mycotoxin is a common contaminant of various feedstuffs and of foodstuffs such as grains, coffee and wine. The levels of OTA have been established in 122 South African wines, representative of a variety of wine cultivars from various wine-producing regions of the country. The method of analysis was based on the method of Visconti et al. (1999): it consisted of immunoaffinity clean up, quantification on reversed phase HPLC with fluorescence detection and confirmation of the presence of OTA by synthesising its methyl ester.  The levels of OTA of most of the red and white wines were substantially lower than the maximum permissible levels of OTA in wines, as suggested by the European Union. However, high levels of OTA were found in a few noble late harvest wines. This first comprehensive survey unambiguously shows that OTA presents no cause for concern to the South African wine industry.